Associations between the rate, amount, and composition of weight loss as predictors of spontaneous weight regain in adults achieving clinically significant weight loss: A systematic review and meta‐regression. (29th March 2019) - Turicchi, Jake; O'Driscoll, Ruairi; Finlayson, Graham; Beaulieu, Kristine; Deighton, Kevin; Stubbs, R. James
Summary: Weight regain following weight loss is common although little is known regarding the associations between amount, rate, and composition of weight loss and weight regain. Forty‐three studies (52 groups; n = 2379) with longitudinal body composition measurements were identified in which weight loss (≥5%) and subsequent weight regain (≥2%) occurred. Data were synthesized for changes in weight and body composition. Meta‐regression models were used to investigate associations between amount, rate, and composition of weight loss and weight regain. Individuals lost 10.9% of their body weight over 13 weeks composed of 19.6% fat‐free mass, followed by a regain of 5.4% body weight over 44 weeks composed of 21.6% fat‐free mass. Associations between the amount ( P  < 0.001) and rate ( P  = 0.049) of weight loss and their interaction ( P  = 0.042) with weight regain were observed. Fat‐free mass ( P  = 0.017) and fat mass ( P  < 0.001) loss both predicted weight regain although the effect of fat‐free mass was attenuated following adjustment. The amount ( P  < 0.001), but not the rate of weight loss ( P  = 0.150), was associated with fat‐free mass loss. The amount and rate of weight loss were significant and interacting factors associated with weight regain. Loss of fat‐free mass and fat mass explained greater variance in weight regain than weight loss alone.